The Effect of Combination of Turmeric and Black Pepper Extracts in Osteoarthritis of the Knee - Zahraa Matheel Nasir; Haidar M. Jawad; Sami S. Salman (Institute of Medico-legal Publications Pvt Ltd, 2021)
The management of osteoarthritis (OA) remains a challenge. Curcumin is basically a spice that is known for its anti-inflammatory properties. In vitro studies suggest that curcumin could be beneficial for cartilage in OA. Piperine, derived from black pepper, is added to Curcumin to increase its bioavailability. The aim of this randomized, double blind trial was to evaluate the effects of combination curcumin plus piperine in knee OA patients.A total of 43patients were randomly assigned to receive the fixed dose combination (curcumin 500 mg plus piperine 5 mg) or placebo twice daily for three months and was evaluated using a Western Ontario MacMaster (WOMAC) score. Results revealed the serum levels of High Sensitivity C - reactive protein (HS-CRP)and Human Cross Linked C-Telopeptide of Type II Collagen (CTX-II) were changedafter 3 months of treatment. In conclusions: The treatment with curcumin was globally well tolerated. It significantly decreased the WOMAC score and NSAIDS uses. Serum level of CTXII significantly reduced (p<0.001) and tended to decrease serum HS-CRP. In addition, curcumin significantly reduced body mass index,this may point toward that curcuminoids has role in weight reduction,and hence, lower risk of OA